The Harms of Imagining the Ideal - Chen, Stacy (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
In this response to the commentary “Disabling Bioethics Futures”, I offer support for the author’s argument that bioethics theory and pedagogy ought to be reframed to better incorporate the perspectives of disabled persons. Specifically, I argue that it is not only a pedagogical flaw but an active harm when bioethics pedagogy preserves disrespectful or discriminatory views by using outdated literature.